Physiological basis of sports training system development among boxers - Nazarenko, L. D.; Kolesnik, I. S.; Osipov, D. A. (The Russian Journal of Physical Education and Sport, 2017)
The effectiveness of competitive activity in boxing is provided by a constant development of educational methodology and training; by the search for the means of general physical and special readiness level increase; by the leading motional- coordinating qualities development, which condition the character of motional activity; by the working capacity of a sportsman, readiness to stand the attack of the opponent. During the process of sports training development among combatants great attention should be paid to psychological readiness improvement to struggle with the opponent, who is higher, stronger, and more aggressive. The skills formation of different defensive techniques effective use is very important for the sportsmanship improvement among boxers, as a rational use of these techniques helps to avoid timely the opponent`s attacking actions.Material. Theoretical and methodical importance substantiation of physiological mechanisms use in the system of sports training development among boxers. Research methods: scientific and scientific-methodical literature analysis and summarizing, pedagogical experiment, testing, method of expert evaluations, analytical methods. Results. The skills formation of motional actions afferent synthesis, the main components of which are motivation, memory, situational and start-up information, helps more effectively use motivation of going in for boxing as the means of many-sided harmonious physical and spiritual-moral development. Different kinds of memory use (mechanical, logical, short-term memory,long-term memory, motional) provides competitive activity experience formation, self-confidence increase, readiness to realize accumulated motional potential in difficult conditions of combat with the unknown, highly-qualified opponent. The skills of situational and start-up information use provides the set aim achievement in terms of uncustomary location of the ring, great amount of the audience with an inadequate reaction to the situation on a boxing ring and in terms of not objective refereeing. Owing to the skills formation of situational and start-up information use a sportsman is successful in terms ofrepeated program of actions, attack fulfillment in case of time deficiency, an adequate reaction to a single start-up signal. Conclusion. Taking into consideration physiological basis of sports training improvement process among boxers, as the results of the pedagogical experiment prove, provides the training process effectiveness increase.